Cultural and Organizational Climate Factors Modifiers of the Performance of the University Academic Worker: an Adjusted Structural Model - Barrera Ovando, César Enrique; Chán Quijano, José Guadalupe; Hernández Triano, Leonardo (HITOS DE CIENCIAS ECONÓMICO ADMINISTRATIVAS, 2023)
OBJECTIVE: Identify and select factors of the organizational climate and culture variables that affect university teaching performance to develop an information collection instrument and verify that the instrument measures and adjusts to partial and integral conceptual models.MATERIAL AND METHOD: Non-experimental quantitative cross-sectional research at a confirmatory correlational level. An information collection instrument was designed and elaborated based on the empirical evidence found in a literary review and the state of the art of the investigated variables. After carrying out the validation of experts and a pilot to 67 university professors, it was determined through the SPSS software ver. 24, the reliability of the instrument and the multivariate analysis. The structure of the instrument was adapted, proceeding to the field investigation with a sample of 257 cases using the AMOS ver. software. 24, the structural model of the study was made by adjusting the model and checking its discriminant validity.RESULTS: The calculations obtained through the analysis of structural equations showed that, implicitly, the constructs established in the models reflect the items in the questionnaire.CONCLUSIONS: The instrument designed and built reflects the dimensions that are being measured, confirming that the study model can be used in further research.
Keywords: Multivariate analysis; Organizational culture; Organizational climate; Professional performance; Structural equations.